PELATIHAN PENTINGNYA PENCATATAN KEUANGAN, STRATEGI PEMASARAN ONLINE DAN DESAIN KEMASAN PRODUK PADA USAHA MARNING JAGUNG - Ita Rifiani Permatasari; Anik Kusmintarti; Baroroh Lestari; Becik Gati A; Jatrifia Ongga S (Jurnal Pengabdian kepada Masyarakat, 2020)
This community service aims to increase corn marning business income, at the Corn Marning Center in Kecamatan Pandanwangi, Kampung Simpang Teluk Bayur, Kota Malang. The Corn Marning Center in Malang City is a family business, which was initiated in the 1980s, and the business management is still simple. Not yet using a financial recording system, because they think financial records are not important. The marketing system is still simple, which only relies on an order system and waits for consumers to come, as well as the product's marketability is still simple.The partners of this service are UMKM which have a Corn Marning business, starting from the process of making Corn Marning to selling it in their own shops, namely Toko Cahaya and Toko Adnan. The purpose of this PKM-Kemitraan is to provide knowledge about the Concept of Financial System Recording by using a simple program, making it easier for UMKM to record and understand the financial system, provide training on online marketing and manufacturing of more modern product packaging, and providing equipment assistance in the form of Pedal Sealer Machines needed by both UMKM. At the end of the activity, it will be evaluated, by providing assistance and monitoring based on the results of financial records, making online marketing and making product packaging for 1 month.